2015
DOI: 10.3390/molecules20022445
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds of Raspberry Fruit: From Analytical Methods to Biological Role and Sensory Impact

Abstract: Volatile compounds play a key role in the formation of the well-recognized and widely appreciated raspberry aroma. Studies on the isolation and identification of volatile compounds in raspberry fruit (Rubus idaeus L.) are reviewed with a focus on aroma-related compounds. A table is drawn up containing a comprehensive list of the volatile compounds identified so far in raspberry along with main references and quantitative data where available. Two additional tables report the glycosidic bond and enantiomeric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 80 publications
2
60
0
1
Order By: Relevance
“…In other words, different raw materials and processes can develop unique compounds which can be responsible for variety or process specific aromas. With regards to raw materials, Aprea et al noticed a similar effect in raspberries (Aprea, Biasioli, & Gasperi, 2015), where large qualitative and quantitative differences in the odor active compound profile were observed in different varieties, crop years, and post-harvest treatments. In peanuts, large organoleptic and volatile profile differences have also been observed due to processing (microwaving) (Schirack et al, 2006b).…”
Section: Aroma Active Compounds Versus Aroma Fingerprint -Compound Comentioning
confidence: 78%
“…In other words, different raw materials and processes can develop unique compounds which can be responsible for variety or process specific aromas. With regards to raw materials, Aprea et al noticed a similar effect in raspberries (Aprea, Biasioli, & Gasperi, 2015), where large qualitative and quantitative differences in the odor active compound profile were observed in different varieties, crop years, and post-harvest treatments. In peanuts, large organoleptic and volatile profile differences have also been observed due to processing (microwaving) (Schirack et al, 2006b).…”
Section: Aroma Active Compounds Versus Aroma Fingerprint -Compound Comentioning
confidence: 78%
“…In raspberry fruit (Rubus idaeus L.), phenolic compounds only represent 1% of the total lavor compounds (Figure 3), whose concentration varies between "trace amount" and 0.3 mg/kg [73]. Nevertheless, in wild berries, several volatile phenolic compounds were identiied by Honkanen et al [73], such as 2-methoxy-4-vinylphenol, 2-methoxy-5-vinylphenol, 3,4-dimethoxybenzaldehyde, and 4-vinylsyringol, none of which have been reported in cultivated varieties [74]. An important fact stated by Honkanen et al [73] is that with the exception of ionones, the amounts of individual volatile compounds in wild raspberries were generally three to four times higher than in the cultivated varieties.…”
Section: Impact Of Fruit Phenolic Compounds On Sensorial Characteristicsmentioning
confidence: 99%
“…Such a study has been run on Runner type peanuts Da Conceicao Neta, 2010), but the results of this thesis here suggest it may be worth repeating with different market types (i.e. species of Arachis): Chapter 3 showed that several compounds which were in fact correlated to sensory attributes were not present in all samples, while Aprea et al noticed a similar effect in raspberries (Aprea, Biasioli, & Flavia Gasperi, 2015), where large qualitative and quantitative differences in the odour active compound profile was observed in different varieties, crop years, and post-harvest treatments. It is therefore possible that the current understanding of odour active compounds in peanuts is incomplete, as it is based on Arachis Hypogaea only, and not Arachis Fastigiata or other commonly cultivated species.…”
Section: Methodological Limitations 64mentioning
confidence: 82%
“…In other words, different raw materials and processes can develop unique compounds which can be responsible for variety or process specific aromas. With regards to raw materials, Aprea et al noticed a similar effect in raspberries (Aprea, Biasioli, & Flavia Gasperi, 2015), where large qualitative and quantitative differences in the odour active compound profile was observed in different varieties, crop years, and post-harvest treatments. In peanuts, large organoleptic and volatile profile differences have also been observed due to processing (microwaving) ).…”
Section: Aroma Active Compounds Versus Aroma Fingerprint -Compound Comentioning
confidence: 83%
See 1 more Smart Citation